EFEKTIVITAS PENDEKATAN PEER SUPPORT DALAM MENINGKATKAN KETERAMPILAN BERBICARA ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Eva G. Siringo-ringo; Febina Maharani Tarigan; Fitri First Nova Butarbitar; Novita Ariska Barus; Tiara Lira Simanjorang; Lili Tansliova; Anggia Puteri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This literature review explores the effectiveness of the peer support approach in improving the speaking skills of children with special needs (CWSN) in inclusive school settings. Communication barriers often hinder the academic and social development of CWSN, especially in verbal interactions. Peer support, rooted in social learning theory and the zone of proximal development, provides a natural and empathetic learning environment through structured interaction with peers. The findings of this study indicate that various models—such as peer tutoring, peer buddy systems, and peer-mediated instruction—significantly enhance verbal engagement, vocabulary acquisition, and social participation among CWSN. In addition to improving linguistic abilities, peer support also contributes to emotional security, reduces anxiety, and fosters a sense of belonging. Despite some implementation challenges, such as lack of training and institutional support, the peer support strategy proves to be a powerful tool in promoting inclusive and equitable education. This paper highlights best practices and offers practical implications for integrating peer support as a sustainable component of inclusive classroom pedagogy.